Empirical Analysis of Destination Image Through Tiktok Video Comments - Sobarna, Aditia (Politeknik Negeri Bandung, 2023)
This study examines the role of comments on the TikTok social media platform in shaping the image of tourist destinations, focusing on Borobudur Temple, a world heritage site in Indonesia. A thematic analysis of comments on TikTok reveals the public's perception of Borobudur Temple as a historical destination enriched with spiritual values and myths. Terms such as